2015
DOI: 10.1371/journal.pone.0134090
|View full text |Cite
|
Sign up to set email alerts
|

Mycelial Mattress from a Sporangia Formation-Delayed Mutant of Rhizopus stolonifer as Wound Healing-Enhancing Biomaterial

Abstract: A mycelial mattress of Rhizopus stolonifer obtained from a liquid static culture was utilized for wound dressing and biomedical use. Following screening of mutants induced by UV radiation, F6, exhibiting delayed sporangium formation was selected because its sporangium maturation exhibited a 5-day delay without significant loss of mycelial weight compared to the wild type. The sporangium-free mycelial mattress from the sporangiospore culture of F6 was treated with 1N sodium hydroxide at 85°C for 2 h to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The in vivo studies also confirmed the wound healing efficacy of the mycelial mattress (Fig. 5) (Chien et al, 2015) indicated by the epidermal layer formation and resemblance of the healed wound to normal skin.…”
Section: Chitin and Chitosansupporting
confidence: 70%
See 1 more Smart Citation
“…The in vivo studies also confirmed the wound healing efficacy of the mycelial mattress (Fig. 5) (Chien et al, 2015) indicated by the epidermal layer formation and resemblance of the healed wound to normal skin.…”
Section: Chitin and Chitosansupporting
confidence: 70%
“…Additionally, as P. blakesleeanus sample, which had the highest chitin content (91%), showed better proliferation activity than that of A. oryzae with a chitin content of 37%, indicating that the proliferative impact could be associated with their chitin quantity (Chung et al, 1994). Also, Mei-Yin Chien et al showed that a chitin-containing mycelial mattress of Rhizopus stolonifera (called Rhizochitin) can be used for wound dressing (Chien et al, 2015).…”
Section: Chitin and Chitosanmentioning
confidence: 99%
“…Examples are the Saccachitin reported by Su and colleagues and the Rhizochitin produced by Chien et al . , where the chitin extracted from mycelia is casted in membranes tested as skin substitute and for the growth of fibroblasts 49 , 50 or for its immunomodulatory activity 93 .…”
Section: Resultsmentioning
confidence: 99%
“…Membranes produced by simply casting these extracts, such as the Saccachitin reported by Su et al 49 and the Rhizochitin produced by Chien et al . 50 , showed positive effects on fibroblast and keratinocytes growth. As far as we know, only the work by Narayanan et al .…”
Section: Introductionmentioning
confidence: 97%
“…Another process included the mycelium isolation of a non-dikaryotic species called Rhizopus stolonifera . The sporangia-producing mucoromycete was studied for the creation of a thick “mycelium mattress” that was deproteinized and dried for wound healing purposes [ 2 , 111 ].…”
Section: Leveraging Unique Species For Pmmsmentioning
confidence: 99%